Good citizen: how a younger generation is reshaping American politics - "Dalton, Russell J" (Washington D.C., 2009)
Focusing on the 2008 presidential election, this title answers questions that are sure to resonate with your students and provide great fodder for lively discussion: Should we be surprised by Obama's appeal to the young engaged citizens? What were the sources of this appeal? And who voted for Obama in November?
Keywords: Citizenship-United States